The clinical impact of paroxysmal arrhythmias on the hospital outcomes of patients admitted with cirrhosis: propensity score matched analysis of 2011–2017 US hospitals. (3rd October 2021) - Lee, David Uihwan; Fan, Gregory Hongyuan; Hastie, David Jeffrey; Addonizio, Elyse Ann; Karagozian, Raffi
ABSTRACT: Background: We evaluate the effects of paroxysmal arrhythmia on the hospital outcomes of patients admitted with cirrhosis. Research design and methods: 2011–2017 National Inpatient Sample was used to isolate patients with decompensated/compensated cirrhosis, stratified by paroxysmal arrhythmia (supraventricular: PSVT and ventricular: PVT). The cohorts were matched using propensity-score matching and compared to mortality, length of stay, cost, and cardiac complications (cardioversion, cardiogenic shock, cardiac arrest, and ventricular fibrillation). Results: In compensated cirrhosis, 2, 453 had PSVT with matched controls; 5, 274 had PVT with matched controls. Those with PSVT had higher mortality (aOR 1.55 95%CI 1.23–1.95) and higher rates of cardioversion and cardiogenic shock; likewise, those with PVT had higher mortality (aOR 2.41 95%CI 2.09–2.78) and higher rates of all complications. In decompensated cirrhosis, 1, 598 had PSVT with matched controls; 4, 178 had PVT with matched controls. Those with PSVT had higher mortality (aOR 1.57 95%CI 1.28–1.93) and higher rates of cardioversion, cardiogenic shock, cardiac arrest; those with PVT had higher mortality (aOR 2.25 95%CI 1.98–2.56) and higher rates of all complications. Conclusion: The findings from this study show that in either decompensated or compensated cohort, those with paroxysmal arrhythmias are at a higher risk of in-hospital mortality and adverse cardiac outcomes.